Left cheek sclerosing rhabdomyosarcoma and development of isolated free flap donor site metastasis. Issue 4 (7th April 2022) - Zhou, Deborah; Bhadri, Vivek; Luk, Peter; Ch'ng, Sydney; Franks, Daniel; Hong, Angela
Abstract : Rhabdomyosarcoma is a rare mesenchymal malignancy with four different morphological subtypes: alveolar, embryonal, pleomorphic and spindle cell/sclerosing. It is the most common soft tissue sarcoma of children and adolescents but occurs less commonly in adults. We describe a male patient in his 20s with sclerosing rhabdomyosarcoma of the left cheek who developed an isolated free flap donor site metastasis in the first instance but subsequently progressed with bilateral pulmonary metastases. Multidisciplinary team involvement in a sarcoma specialist centre is essential and collaboration between the pathologist, radiologist, head and neck surgeon, orthopaedic surgeon, radiation oncologist and medical oncologist were integral in providing optimal management in this patient. Furthermore, this case report highlights this phenomenon of implantation metastasis in a patient with rhabdomyosarcoma, and emphasises the importance of surgical barriers between the resection and reconstruction teams in an oncological case.